Removal of volatile organic compounds from Waste air stream of a furniture factory. (December 2020) - Silva, João R.; Ascensão, Dânia S.; Castro, Luís M.
Abstract: In this paper, an alternative to the thermal oxidation of VOC in a gaseous effluent was studied, to lessen power consumption and mitigate the environmental impact of a furniture factory located in the north of Portugal. A gas–liquid absorption of n-butyl acetate in a packed-bed column of LECA was studied to achieve a VOC outlet in agreement with the Portuguese law for effluent discharge in the atmosphere. Studies of VOC physical absorption with water were evaluated. Experiments with a continuous flow of tap water demonstrated to be very effective in removing n-butyl acetate of the air stream. Efficiencies over 90% were achieved by this method and in three experiments outlet VOC concentration remained under the imposed limit of 50 mg C /Nm 3 . Other experiments were registered to be above the imposed limit, even so, they were also highly effective, suggesting that if the outlet water can be reused and employed for other purposes, this solution might have an industrial interest. In the other studied approach, with a closed water circuit, the system proved to be less effective, with the removal efficiency of the VOC dropping very fast, which revealed the need for continuous treatment of the recirculated water. When introducing the microorganisms to the system, the efficiency was lower than for open circuit, averaging, 40.2%, 27.0%, 25.5%, respectively in the three experiments realized, suggesting that the system might be an interesting and a sustainable alternative to the ROT system employed at the factory, with a significant reduction in the energy consumption.